2011
DOI: 10.1007/s10750-011-0782-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flooding on carbon and nutrient standing stocks of helophyte biomass in rewetted fens

Abstract: Rewetting can strongly affect the matter balance of peatlands. Owing to evidence of increasing CH 4 emissions and P mobilisation after rewetting, the effects of peatland restoration on climate, eutrophication risks and related controversies are discussed. Our study focuses on the role of helophytes in the carbon and nutrient balance of rewetted fen grasslands of NE Germany. We hypothesise that the helophytes Carex riparia, Glyceria maxima, Phalaris arundinacea, Phragmites australis and Typha latifolia differ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…For instance, [41] reported an almost continuous increase in aboveground biomass of common reed in Sweden from May to August, when the yield peaked. The same pattern was also observed by [42] in their study conducted in Germany, in which they found the highest yield in August, while [43] in northeastern Germany found a biomass yield peak in July. Since the phenology and crop productivity of common reed are highly dependent on temperature [44], the unlimited supply of water provided by the paludiculture conditions, and the high amounts of nutrients due to the eutrophication of the drainage water make possible a longer vegetative season under Mediterranean conditions, thus explaining the biomass peak recorded in September.…”
Section: Discussionsupporting
confidence: 81%
“…For instance, [41] reported an almost continuous increase in aboveground biomass of common reed in Sweden from May to August, when the yield peaked. The same pattern was also observed by [42] in their study conducted in Germany, in which they found the highest yield in August, while [43] in northeastern Germany found a biomass yield peak in July. Since the phenology and crop productivity of common reed are highly dependent on temperature [44], the unlimited supply of water provided by the paludiculture conditions, and the high amounts of nutrients due to the eutrophication of the drainage water make possible a longer vegetative season under Mediterranean conditions, thus explaining the biomass peak recorded in September.…”
Section: Discussionsupporting
confidence: 81%
“…Short grass species are known to suffer most from the short-term negative effects of flooding [ 54 ] and are less able to recover [ 55 ]. According to Kvet (1984; in [ 56 ]), the growth of wetland sedges ( Carex spp.) is favored by low inundation levels and hampered by high inundation.…”
Section: Discussionmentioning
confidence: 99%
“…The latter we observed especially at low inundation levels and it was most pronounced where vegetation suffered from the heaviest die-back (cluster NW-). Schulz et al [ 56 ] found that helophyte species like e.g. Carex riparia or Phragmites australis store considerable amounts of carbon and temporarily withdraw high amounts of nutrients from the top soil during the growing season; elements that will be released when vegetation dies back.…”
Section: Discussionmentioning
confidence: 99%
“…Cutting removes only the aboveground part of the plant, which is not essential for peat formation in fens as it rapidly decomposes under natural (no-use) conditions (Schulz et al, 2011;Wichtmann & Tanneberger, 2011). Cutting has been shown to increase aboveground biomass production in Phragmites (Gran eli, 1989;Ostendorp, 1999) and Carex (G€ usewell et al, 1998).…”
Section: Introductionmentioning
confidence: 99%